Metabolic dysfunction-associated steatotic liver disease and hepatocellular carcinoma: Challenges in clinical practice - Osmański, Radosław; Litwiniuk, Maria; Mardas, Marcin; Stelmach-Mardas, Marta (Clinical and Experimental Hepatology, 2025)
The number of patients whose chronic metabolic liver disease leads to the development of hepatocellular carcinoma (HCC) is increasing. In patients with non-alcoholic fatty liver disease (NAFLD), HCC can arise in both cirrhotic and non-cirrhotic livers. This complicates appropriate surveillance and causes HCC to be diagnosed at a more advanced stage. Current therapeutic guidelines do not take into account the etiology of HCC when selecting the type of systemic treatment, as the data on the effectiveness of immunotherapy in HCC caused by metabolic dysfunction associated steatotic liver disease (MASLD) are insufficient and come from post-hoc subgroup analysis in phase 3 trials. In order to improve survival in the group of patients with chronic liver disease and metabolic disorders, it is crucial to use non-pharmacological and pharmacological methods to prevent progression of fatty liver disease, treat comorbidities with modification of cardiometabolic risk factors, and implement effective programs for early detection of HCC.